2005
DOI: 10.1203/01.pdr.0000148068.32201.50
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Secretion of Cathelicidin Antimicrobial Peptides in Murine Mammary Glands and Human Milk

Abstract: Mammalian milk possesses inherent antimicrobial properties that have been attributed to several diverse molecules. Recently, antimicrobial peptides that belong to the cathelicidin gene family have been found to be important to the mammalian immune response. This antimicrobial is expressed in several tissues and increased in neonatal skin, possibly to compensate for an immature adaptive immune response. We hypothesized that the mammary gland could produce and secrete cathelicidin onto the epithelial surface and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
66
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 37 publications
2
66
1
Order By: Relevance
“…Lysozyme, lactoferrin and lactoperoxidase each possess the ability to suppress the growth of certain bacteria and were identified as minor milk proteins in the early part of the twentieth century . More recently, it has become apparent that milk also contains a range of additional antimicrobial proteins and peptides, including members of the b-defensin, complement, cathelicidin and S100 calgranulin families, as well as several acute phase proteins (Eckersall et al, 2001;Jia et al, 2001;Rainard, 2003;Swanson et al, 2004;Murakami et al, 2005;Lutzow et al, 2008). The role that two of these effector proteins play in contributing to the host-defence function of milk is described below, drawing on previously published work as well as our own unpublished data.…”
Section: Effector Proteins In Cows' Milkmentioning
confidence: 99%
“…Lysozyme, lactoferrin and lactoperoxidase each possess the ability to suppress the growth of certain bacteria and were identified as minor milk proteins in the early part of the twentieth century . More recently, it has become apparent that milk also contains a range of additional antimicrobial proteins and peptides, including members of the b-defensin, complement, cathelicidin and S100 calgranulin families, as well as several acute phase proteins (Eckersall et al, 2001;Jia et al, 2001;Rainard, 2003;Swanson et al, 2004;Murakami et al, 2005;Lutzow et al, 2008). The role that two of these effector proteins play in contributing to the host-defence function of milk is described below, drawing on previously published work as well as our own unpublished data.…”
Section: Effector Proteins In Cows' Milkmentioning
confidence: 99%
“…LL-37 is a human cationic, amphipathic host defense peptide released by proteinase 3 proteolytic processing of the COOH-terminal domain of the human cathelicidin, human cationic antimicrobial protein-18 (6). LL-37 is found in the secondary granules of neutrophils (7), is endogenously expressed by a variety of cells including keratinocytes and epithelial cells, and is released in response to multiple inflammatory stimuli (8,9). On release, LL-37 acts as an effector molecule of innate immunity, displaying anti-infective and immunomodulatory activities, including the induction of neutrophil, CD4 + T-cell and monocyte chemotaxis (10), mast cell activation (11), and neutrophil survival (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Production and secretion of cathelicidin is not restricted to myeloid cells, however. It occurs also in other cells exposed to microbes, such as the epithelial cells of the mouth, tongue, esophagus, intestine, cervix and vagina (13), lung (14), and salivary, sweat (15), and mammary glands (16). Liu et al (4) pursued a remarkable species difference: In mice it had been shown that the acute antimicrobial response triggered by the heterodimer TLR2/1 depends on the generation of nitric oxide (NO) (17), yet in human macrophages the antimicrobial activity of macrophages triggered by TLR 2/1 is not dependent on the generation of NO and obviously must be mediated by alternative effectors.…”
mentioning
confidence: 99%